TTWO-DIMENSIONAL NMR SPECTROSCOPIC STUDY OF SCHIFF BASES DERIVED FROM 4-AMINOANTIPYRINE - Zamorano, Sergio (2017)
There has been the structural analysis of six derivatives of the 4- aminoantipyrine(4AAP) by means of two techniques of two-dimensional NMR, the HSQC and HMBC, which helped to elucidate the structure of four derivatives using the data provided by the interaction between the atoms of carbon and hydrogen present in the different molecules.